Perancangan Media Promosi Colar Living Berbasis Fotografi (International Forum of Researchers and Lecturers, 2024)
Colar Living is a part of the Colar Creative Industry that focuses on the sale of kitchenware products made from teak wood. The issue faced by Colar Living is that this brand is relatively new, having started its business for only 3 months, which reduces consumer trust in the products sold through e-commerce. Additionally, some product photos displayed on Tokopedia are less appealing. A more professional product photography process is required to attract buyers and enhance consumer confidence in purchasing these kitchenware products. The methods employed to address the issues faced by Colar Living include interviews, observations, and discussions. The results of the Colar Living product photography process increase consumer confidence when purchasing products and also boost the sales of Colar Living products. The findings of this research are expected to provide insights for Small and Medium Enterprises (UMKM) entrepreneurs who are just starting their businesses to pay attention to product photography.